Tradisi Kawin Tangkap (Piti Rambang) Suku Sumba di Nusa Tenggara Timur - Elanda Welhelmina Doko; I Made Suwitra; Diah gayatry Sudibya (Warmadewa Press, 2021)
The tradition of capture marriage (Pitti Rambang) of the Sumbanese tribe in East Nusa Tenggara still exists and is carried out continuously with the forced marriage of Sumba women which causes the victim to experience physical, sexual, psychological and social violence. That a strong and inevitable tradition in the culture of the Sumbanese people, who still have a patriarchal culture, upholds customs and this culture facilitates the men. The purpose of this study was to examine the existence of the tradition of mating capture (Pitti Rampang) of the Sumbanese tribe in East Nusa Tenggara and to discuss the factors that influence interbreeding. The methods in this research are the statutory approach, the customary law approach, the concept approach, the legal sociology approach, and the case approach. The results showed that the occurrence of capture marriages (Pitti Rambang) was due to economic factors related to debt, social strata, trust and the level of understanding of the Sumbanese indigenous people towards positive law and the settlement process in this capture marriage was carried out through adat, namely from the stages of search, close the shame, knock on the door, traditional mats, religion (for those of other religions outside the Moruyu belief) until the final stage.